IPO Performance: A Cross-Country Comparison of the Effect of Regulations - Krishnan, CNV; He, Yu (Journal of Accounting and Finance, 2022)
We compare short-term returns around IPOs, as well as longer-term returns and post-issue performance, between US and China IPOs. Short-term abnormal returns are higher for China IPOs than US IPOs, both in univariate tests (difference of means and medians tests), and in multivariate tests, controlling for other variables and fixed effects. We postulate that this is due to the different regulations between the two countries that could lead to more underpricing and constraints on reaching true value, in the short run, for China IPOs. However, the upward price pressure leading to superior stock returns does not last. In the longer-term, not only do China and US IPO firms have similar abnormal stock returns – on average negative as documented in the extant literature - but also the firms’ operating performance, on average, as well as their book-to-market ratios (a proxy for future growth options) are not significantly different, in both univariate and multivariate tests.